On practice and contradiction - Tse-tung, Mao (Revolutions (London, England), 2007)
These early philosophical writings underpinned the Chinese revolutions and their clarion calls to insurrection remain some of the most stirring of all time. Drawing on a dizzying array of references from contemporary culture and politics, Zizek's firecracker commentary reaches unsettling conclusions about the place of Mao's thought in the revolutionary canon.